Absence of Endochondral Ossification and Craniosynostosis in Posterior Frontal Cranial Sutures of Axin2(−/−) Mice - Behr, Björn (Public Library of Science, 2013)
During the first month of life, the murine posterior-frontal suture (PF) of the cranial vault closes through endochondral ossification, while other sutures remain patent. These processes are tightly regulated by canonical Wnt signaling. Low levels of active canonical Wnt signaling enable endochondral ossification and therefore PF-suture closure, whereas constitutive activation of canonical Wnt causes PF-suture patency. We therefore sought to test this concept with a knockout mouse model. PF-sutures of Axin2(−/−) mice, which resemble a state of constantly activated canonical Wnt signaling, were investigated during the physiological time course of PF-suture closure and compared in detail with wild type littermates. Histological analysis revealed that the architecture in Axin2(−/−) PF-sutures was significantly altered in comparison to wild type. The distance between the endocranial layers was dramatically increased and suture closure was significantly delayed. Moreover, physiological endochondral ossification did not occur, rather an ectopic cartilage appeared between the endocranial and ectocranial bone layers at P7 which eventually involutes at P13. Quantitative PCR analysis showed the lack of Col10α1 upregulation in Axin2(−/−) PF-suture. Immunohistochemistry and gene expression analysis also revealed high levels of type II collagen as compared to type I collagen and absence of Mmp-9 in the cartilage of Axin2(−/−) PF-suture. Moreover, TUNEL staining showed a high percentage of apoptotic chondrocytes in Axin2(−/−) PF-sutures at P9 and P11 as compared to wild type. These data indicated that Axin2(−/−) PF-sutures lack physiological endochondral ossification, contain ectopic cartilage and display delayed suture closure.